Physical Exercise Preserves Adult Visual Plasticity in Mice and Restores it after a Stroke in the Somatosensory Cortex - Kalogeraki, Evgenia; Pielecka-Fortuna, Justyna; Hüppe, Janika M.; Löwel, Siegrid (Frontiers in Aging Neuroscience, 2016)
The primary visual cortex is widely used to study brain plasticity, which is not only crucial for normal brain function, such as learning and memory, but also for recovery after brain injuries such as stroke. In standard cage raised mice, experience-dependent ocular dominance plasticity in the primary visual cortex declines with age and is compromised by a lesion in adjacent and distant cortical regions. In contrast, mice raised in an enriched environment exhibit lifelong ocular dominance plasticity and are protected from losing ocular dominance plasticity after a stroke-lesion in the somatosensory cortex. Since standard cage mice with an access to a running wheel displayed preserved ocular dominance plasticity during ageing, we investigated whether physical exercise might also provide a plasticity promoting effect after a cortical stroke. To this end, we tested if adult running wheel-raised mice preserved ocular dominance plasticity after stroke and also if short-term running after stroke restored ocular dominance plasticity to standard cage mice. Indeed, unlike mice without a running wheel, adult running wheel mice continued to show ocular dominance plasticity even after stroke, and a two weeks running wheel experience after stroke already restored lost ocular dominance plasticity. Additionally, the experience-enabled increase of the spatial frequency and contrast threshold of the optomotor reflex of the open eye, normally lost after stroke, was restored in both groups of running wheel mice. Our data suggest that physical exercise alone can, not only preserve visual plasticity into old age but also restore it after a cortical stroke.